Analisis Perilaku Anggota Koperasi dalam Pembelian Barang pada KUD Karya Agung Kecamatan Singingi Kabupaten Kuantan Singingi - Muhammad Irwan (Politeknik Ganesha Medan, 2020)
This research was conducted at KUD Karya Agung located in Sumber Datar Village, Kec. Singingi Kab. Kuantan Singingi. The purpose of this study is to determine what factors influence the behavior of cooperative members in making decisions to buy goods at KUD Karya Agung. While the benefits that the author can provide to cooperatives are as input or information for KUD Karya Agung management regarding the behavior of cooperative members in making decisions to buy goods offered by cooperatives.Based on the formulation of the problem and the purpose of the study, the authors propose a hypothesis that is suspected of the behavior of cooperative members in making decisions to buy goods in the KUD Karya Agung influenced by factors of culture, social class, attitude and psychology. From the research conducted by the author, an opportunity can be taken that the factors that influence the behavior of cooperative members in making decisions to buy goods at KUD Karya Agung are social environmental factors, attitudes and psychology.